2020
DOI: 10.1136/bmjopen-2019-035940
|View full text |Cite
|
Sign up to set email alerts
|

Protocol for a systematic review of health promotion interventions for African Americans delivered in US barbershops and hair salons

Abstract: IntroductionAfrican American adults are disproportionately burdened by chronic diseases, particularly at younger ages. Developing culturally appropriate interventions is paramount to closing the gap in these health inequities. The purpose of this systematic review is to critically evaluate health promotion interventions for African Americans delivered in two environments that are frequented by this population: barbershops and hair salons. Characteristics of effective interventions will be identified and eviden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…The study was registered with the International Prospective Register of Systematic Reviews (PROSPERO) in 2020 (CRD42020159050). The detailed prespecified protocol has been previously published [ 43 ]. Seven databases (Academic Search Ultimate, Cumulative Index of Nursing and Allied Health Literature (CINAHL), Embase, PsychInfo, PubMed, Web of Science, and ProQuest Dissertations from inception to October 2019) were queried following comprehensive search strategies developed in consultation with a medical librarian (Additional file 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…The study was registered with the International Prospective Register of Systematic Reviews (PROSPERO) in 2020 (CRD42020159050). The detailed prespecified protocol has been previously published [ 43 ]. Seven databases (Academic Search Ultimate, Cumulative Index of Nursing and Allied Health Literature (CINAHL), Embase, PsychInfo, PubMed, Web of Science, and ProQuest Dissertations from inception to October 2019) were queried following comprehensive search strategies developed in consultation with a medical librarian (Additional file 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…For example, in a randomized controlled trial by Victor et al (2019) , the authors found a significant blood pressure level reduction among Black male patrons of barbers trained in blood pressure health promotion by clinical nurses. Other health promotion literature has found success in endorsing healthy lifestyles within barbershops and beauty salons (see Palmer et al, 2021 ). Mbilishaka (2018) outlines the intervention called “PsychoHairapy,” which bridges mental health care professionals with beauticians in order to train hair care professionals to improve clients mental health.…”
Section: Barbershops and Beauty Salons In Black Communitiesmentioning
confidence: 99%
“…To the authors of this protocol’s knowledge, there is one known protocol for a systematic review of health promotion interventions for African Americans delivered in barbershops and salons and two completed systematic reviews reviewing the use of peer-based health promotion interventions [ 30 – 32 ]. The protocol for the known systematic review of interventions conducted in barbershops and salons consists of interventions that target both men and women [ 31 ]. Additionally, the protocol focuses on location (i.e., the barbershop), rather than the method (i.e., peer-to-peer model) of delivery for the health promotion effort [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…The protocol for the known systematic review of interventions conducted in barbershops and salons consists of interventions that target both men and women [ 31 ]. Additionally, the protocol focuses on location (i.e., the barbershop), rather than the method (i.e., peer-to-peer model) of delivery for the health promotion effort [ 31 ]. The two known completed systematic reviews provide mixed evidence for the use of peer-to-peer models as a method, though were not restricted to literature examining health promotion efforts specifically targeting African American men [ 30 , 32 ].…”
Section: Introductionmentioning
confidence: 99%